Non-invasive diagnosis of upper airway malignancies based on the analysis of markers in exhaled air - D. E. Kulbakin; E. L. Choynzonov; I. K. Fedorova; E. V. Obkhodskaya; A. V. Obkhodskiy; E. O. Rodionov; V. I. Sachkov; V. I. Chernov (Сибирский онкологический журнал)
The purpose of the study was to evaluate diagnostic capabilities of the gas analysis sensor device used for the study of exhaled gas samples obtained from patients with oropharyngeal and laryngeal cancers.Material and Methods. Exhaled gas samples from 31 oropharyngeal and laryngeal cancer patients and 31 healthy volunteers were studied using a diagnostic device based on the detection of volatile compounds in inhaled air using semiconductor gas sensors with subsequent neural network analysis.Results. Based on the signals from gas sensors, the neural network classified and identified patients with malignant neoplasms. The sensitivity and specificity of the method were 67.74% and 87.1%, respectively.Conclusion. The gas analysis sensor device and the method for detecting oropharyngeal and laryngeal tumors using the exhaled gas analysis are an accessible and cheap diagnostic tools, and are promising for screening the population in order to select individuals for a comprehensive examination (endoscopic, radiological and morphological) in identifying suspicion of cancer.